Learning curve for laparoscopic staging of early and locally advanced cervical and endometrial cancer - Tahmasbi Rad, Morva; Wallwiener, Markus; Rom, Joachim; Sohn, Christof; Eichbaum, Michael H. R. (Archives of gynecology and obstetrics, 2013)
Laparoscopic staging is rapidly evolving as an important surgical approach in the field of gynecology oncology. However, the specific learning curve associated with this approach remains poorly investigated. This study aimed to evaluate the learning curve for laparoscopic staging of uterine cancers.
Gesehen am 13.12.2021